Results of screening and diagnostic stages of epidemiological study of rheumatic diseases social and economic consequences in Tatarstan republic - N G Shamsutdinova; I G Salichov; S F Erdes; S P Yakupova (Научно-практическая ревматология)
Results of screening and diagnostic stages of epidemiological study performed in Tatarstan republic in the context of inter-regional program “Social and economic consequences of rheumatic diseases” (RD) are presented. Objective. To study structure and prevalence of rheumatic diseases. Material and methods. 3272 rural (58,5% female) and 3043 urban (54,6% female) inhabitants were questionnaired. All respondents reported joint swelling and a random part of pts with joint pain were selected and examined. Results. RD were diagnosed in 81,1% (812 persons), non rheumatic diseases – in 8,4% (84 persons), low back pain syndrome – in 6,9% (69 persons), and in 3,7 (37 persons) diseases were not revealed. 498 rural and 504 urban inhabitants with previously revealed osteoarthritis, rheumatoid arthritis or other bone-joint diseases were further examined. Conclusion. Information about structure and prevalence of RD among adult inhabitants of Tatarstan republic with joint complaints was obtained.